Nardo, Ed., The Rise Of Christianity - Kolbaba, Tia (Teaching History: A Journal of Methods, 2001)
The Rise of Christianity is one of a series of anthologies, "Turning Points in World History." The series aims to describe past events that have had "effects and outcomes that change the course of history." This example comprises an introductory essay on the early history of Christianity (down to c. 604); nineteen seminal scholarly essays with contextualizing introductions for each; a selection of primary sources; a secondary bibliography; and an index. The essays range from discussions of the Jewish and Roman contexts of Jesus’s life to a brief survey of Christianity since c. 600.